2001
DOI: 10.1002/jmv.1075
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus sequences resembling coxsackievirus A2 detected in stool and spleen from a girl with fatal myocarditis

Abstract: A 10-year-old girl who died suddenly was found at post mortem to have myocarditis. Virus could not be cultured from post-mortem stool, spleen or heart but enterovirus RNA was detected in stool and spleen by PCR, and the stool caused flaccid paralysis in newborn suckling mice. A 654 base pair (bp) sequence from the capsid-coding region of the viral genome was amplified from an affected mouse and sequenced. Using this sequence, strain-specific nested primers were designed and used to amplify viral sequences dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Recent studies concerning SIDS cases as well as older children detected different viruses in cases of myocarditis using molecular methods to search for the genome sequences of enteroviruses (Bendig et al, 2001;Lau, 1994), adenovirus (Lozinski et al, 1994), parvovirus B19 (Murry et al, 2001), Epstein-Barr virus, and human herpes viruses in clinical or autopsy samples (Towbin et al, 1993). Some authors speculate that there are cases of myocarditis misdiagnosed as SIDS (Shatz et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies concerning SIDS cases as well as older children detected different viruses in cases of myocarditis using molecular methods to search for the genome sequences of enteroviruses (Bendig et al, 2001;Lau, 1994), adenovirus (Lozinski et al, 1994), parvovirus B19 (Murry et al, 2001), Epstein-Barr virus, and human herpes viruses in clinical or autopsy samples (Towbin et al, 1993). Some authors speculate that there are cases of myocarditis misdiagnosed as SIDS (Shatz et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These studies, together with epidemiologic aspects, point to an inflammatory process in cases of sudden infant death syndrome (SIDS) and suggest that new molecular-pathologic methods could lead to an higher incidence of myocarditis. Recent studies also indicate that PCR rapidly detects the presence of viral nucleic acid in a variety of infected tissues and body fluids (Bendig et al, 2001;Lau, 1994;Lozinski et al, 1994;Murry et al, 2001) Enteroviruses are the most common agents of myocarditis. Viral proteins are synthesized as a polyprotein, subsequently cleaved to produce the four capsid proteins VP 1 through VP 4.…”
mentioning
confidence: 99%
“…Consistent with this, acute myocarditis was identified as the cause of death in 39 of 2,560 serial autopsies (ϳ1.5%), but it had been clinically suspected in only one of the cases (11); thus, in this study Ͼ97% of people with lethal myocarditis were free of classical symptoms. Such symptomless myocarditis can cause catastrophic dysfunction of the electrical pathways in the heart, particularly during exertion, and often explains the collapse and death of young and vigorous individuals (12,13). For example, a study of military recruits found that 86% of sudden deaths during basic training occurred during exercise, and 20% were attributable to unsuspected myocarditis (14); overall, it has been estimated that ϳ12% of sudden deaths in individuals of Ͻ40 years of age can be attributed to this disease (6).…”
mentioning
confidence: 99%
“…Acute coxsackievirus infection can cause diseases ranging from mild (rash and myalgia) to severe (pancreatitis, meningitis, and myocarditis). Unsuspected acute viral myocarditis may lead to the collapse and death of young and vigorous individuals, especially during exertion, from catastrophic dysfunction of the electrical pathways in the heart (5,62). Although the majority of symptomatic patients recover well from acute myocarditis, inflammatory events may continue or recur and can have serious long-term sequelae; some 10 to 20% of patients with symptomatic enteroviral myocarditis (ϳ20,000 to 40,000/year in the United States) will develop chronic disease, progressing over time (usually years) to dilated cardiomyopathy (DCM) (38,54), where one or both ventricles dilate and decompensate, with resulting cardiac failure.…”
mentioning
confidence: 99%